Secondary steel mill furnace performance. - Chandra Gupta, Yogesh; bansal, Kamal; N.Sriniwas, S (International Journal of Engineering and Technology, 2018)
Energy in a steel re-rolling mill is mainly consumed in furnaces. Therefore, furnace performance is very important and its contribution in the cost of product is very high. Data has been collected for two different furnaces in Stackle mill and analyzed for performance of furnace. In this paper, effect of furnace performance on secondary steel sector is analyzed. These data about performance is collected on Walking beam furnace in Stackle mill and Re-heating furnace.